The Analyze Financial Performance of PT Gudang Garam Tbk - Abdul Muis, Muhammad; Satria Adhitama (Dinasti Publisher, 2022)
The objective of this research is to analyze the financial performance of pt gudang garam tbk. Using liquidity ratio, solvability ratio, and profitability ratio. The research methodology used is a descriptive quantitative method with time series data and secondary data from the indonesia stock exchange. Mechanical sampling using purposive sampling. The data were analyzed using qualitative comparison of the company financial performance through the comparative approach to the liquidity ratio, solvency ratio, and profitability ratio. The results of the solvency ratio (der) have a good company performance even though it is below the industry average. The results of the calculation of the profitability ratio (npm) have a good company performance because it is above the industry average. The results of the calculation of the profitability ratio (gpm) have poor company performance and are below the industry average. The results of the calculation of the profitability ratio (roe) have a good company performance and are above the industry average. The results of the calculation of the profitability ratio (roi) have a good company performance and are above the industry average.